Future Applications of Intravesical Stem Cell Leukemia (SCL) Gene Transfer for the Treatment of Diabetic Cystopathy - Yan Chen; Jin Sheng Li (Medicine and Medical Research: New Perspectives Vol. 11, 2024)
Diabetic cystopathy, a complication of diabetes affecting the bladder, is mainly characterized by reduced contractility of the detrusor and increased post-voiding residual volume, which is induced by the reduction of the interstitial cells of Cajal. Previous studies have shown that interstitial cells of Cajal (ICCs) in the detrusor have pace-making ability, which is responsible for the contraction of the detrusor. Taken together, increased SCL expression in DCP patients may initiate a cascade of events, resulting in increased c-KIT activity, thus leading to the rescue of bladder function. The c-KIT protein is a specific marker of the interstitial cells of Cajal and the product of a c-KIT proto-oncogene. The interstitial cells of Cajal in a high glucose medium express less c-KIT mRNA and protein. SCL gene serves to assemble SCL complexes on the c-KIT promoter, sustaining c-KIT transcription. Proper transduction of exogenous SCL genetic material, increases c-KIT expression and leads to synthesis of the functional SCL protein. Intravesical, lentiviral vector-mediated gene transfer has been shown efficacious and safe. Therefore, proper intravesical transfer of RNA encoding SCL to the interstitial cells of Cajal may enhance c-KIT transcription and activity in the interstitial cells of Cajal of diabetic bladders, which may improve bladder activity. Therefore, further studies may explore this treatment strategy in detail, not only for diabetic cystopathy but also for other clinical problems, which can ameliorate the quality of life of the patients, and seems therefore valuable.